2012
DOI: 10.1007/s10856-012-4659-6
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelial morphology and organisation after peritoneal treatment with solid and liquid adhesion barriers–a scanning electron microscopical study

Abstract: Separation of traumatized tissue represents the only promising strategy in postoperative adhesion prevention, a relevant clinical problem after surgical intervention. In the present study scanning electron microscopy (SEM) and subsequent morphometry were used to analyse the tissue response to five commercial adhesion barriers. Standardised peritoneal lesions in Wistar rats were covered with solid and viscous barrier materials and semiquantitatively analysed 14 days postoperatively. Striking morphological diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…The implementation of pharmacological substances would transform the concept of solely using physically separating barriers into a material-assisted tissue regeneration by use of highly optimized and functionalized biomaterial systems in the true sense of tissue engineering. 1,4 Besides fibrosis, the foreign body reaction is crucially regulated by macrophages and might be differently influenced by various biomaterials. Regarding the results of this study, it is interesting that there was a negative minimum of the barrier value in the evaluation of granulocytes in the groups treated with Adept and Intercoat.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The implementation of pharmacological substances would transform the concept of solely using physically separating barriers into a material-assisted tissue regeneration by use of highly optimized and functionalized biomaterial systems in the true sense of tissue engineering. 1,4 Besides fibrosis, the foreign body reaction is crucially regulated by macrophages and might be differently influenced by various biomaterials. Regarding the results of this study, it is interesting that there was a negative minimum of the barrier value in the evaluation of granulocytes in the groups treated with Adept and Intercoat.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, SupraSeal was associated with the best adhesion-preventing effect and highest degree of remesothelialization in a scanning electron microscopical study. 1,4 However, to clarify the interplay of inflammation and fibrosis in peritoneal wound healing on the one hand and the influence of barrier materials on these mechanisms on the other, further histological and immunohistochemical studies are necessary. In this context an important limitation of this study have to be seen in the fact, that although a large range of relevant barriers are clinically applied, our study represents only a selection of available materials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18,31–33 Numerous studies have firmly established that peritoneal fibrinolysis is compromised after surgery, either by a reduction in tPA or an increase in its principal inhibitor, plasminogen activator inhibitor-1, 34 or both, indicating that peritoneal fibrin accumulation and stabilization is a key underlying event early in adhesiogenesis. 18,31,32,35 Although our previous studies showed that augmenting the peritoneal fibrinolytic system reduced adhesion formation in a rat model, 1416,19 the coadministration of any of these compounds did not increase adhesion prevention, owing in part, to their mechanistic similarities.…”
Section: Discussionmentioning
confidence: 99%